Characterization of natural rubber/gold nanoparticles SERS-active substrate - Cabrera, Flávio C. [UNESP]; Agostini, Deuber L. S. [UNESP]; Dos Santos, Renivaldo J. [UNESP]; Teixeira, Silvio R. [UNESP]; Rodríguez-Pérez, Miguel A.; Job, Aldo E. [UNESP] (Wiley, 2013)
Natural rubber/gold nanoparticles membranes (NR/Au) were studied by ultrasensitive detection and chemical analysis through surface-enhanced Raman scattering and surface-enhanced resonance Raman scattering in our previous work (Cabrera et al., J. Raman Spectrosc. 2012, 43, 474). This article describes the studies of thermal stability and mechanical properties of SERS-active substrate sensors. The composites were prepared using NR membranes obtained by casting the latex solution as an active support (reducing/establishing agents) for the incorporation of colloidal gold nanoparticles (AuNPs). The nanoparticles were synthesized by in situ reduction at different times. The characterization of these sensors was carried out by thermogravimetry, differential scanning calorimetry, scanning electron microscopy (SEM) microscopy, and tensile tests. It is suggested an influence of nanoparticles reduction time on the thermal degradation of NR. There is an increase in thermal stability without changing the chemical properties of the polymer. For the mechanical properties, the tensile rupture was enhanced with the increase in the amount of nanoparticles incorporated in the material. © 2013 Wiley Periodicals, Inc.
Keywords: biomaterials; elastomers; mechanical properties; nanoparticles; nanowires and nanocrystals; properties and characterization; Active supports; Colloidal gold nanoparticles; Nanowires and nanocrystals; SERS-active substrates; Surface enhanced Raman Scattering (SERS); Surface-enhanced resonance Raman scattering; Tensile ruptures; Ultrasensitive detection; Biological materials; Biomaterials; Characterization; Differential scanning calorimetry; Elastomers; Mechanical properties; Nanoparticles; Nanowires; Raman scattering; Scanning electron microscopy; Sensors; Substrates; Surface scattering; Tensile testing; Thermodynamic stability; Thermogravimetric analysis; Synthesis (chemical)